SPATIAL POLICY IN CENTRAL BORNEO AND THE IMPLICATIONS FOR THE INVESTMENT CLIMATE - Erry Fitrya Primadhany (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2021)
Spatial Plan has a significant influence on economic development in a region caused by many economic functions related to environmental areas that can be used as a means of investment. The issuance of Regional Regulation No. 5 on year 2015 on Provincial Spatial Plan can potentially arise a limited issue of investing.m This study aims to improve spatial policy in central Borneo and look at its implications for the investment climate. This type of research is empirical juridical research with qualitative-descriptive approach. The data analysis method used is descriptive-qualitative. Based on this research, it can be obtained an overview of the spatial policy direction of Central Borneo Province aimed at realizing the spatial order of agriculture-oriented areas of agribusiness and agro-industry, as well as energy barns and food barns while considering the carrying capacity and capacity of the environment. Based on the data obtained, it can be seen that investment realization from year to year has not increased significantly. Spatial policy has an influence on the investment climate in the plantation sector because this sector must occupy the cultivation area or land user area (Area Penggunaan Lahan/LAND USER AREA) in order to run the company. Keywords: Spatial Policy, Investment Climate